ANALISIS STATISTIK DESKRIPTIF TERKAIT PENGGUNAAN FINTECH SYARIAH DI INDONESIA - Yahya, Sahlan; Fianto, Bayu Arie (Universitas Airlangga, 2020)
This research presents a preliminary study on the use of Islamic fintech in terms of several aspects, namely, socio-economic aspects, geographical aspects, social influence, religiosity. Socio-economic aspects consist of gender, age, education level, income level, and type of work. Geographical aspects consist of the distance of residence from the nearest financial institution and location of residence. Data is collected by giving questionnaires to users of Islamic fintech and non-users of Islamic fintech. The results of this study are in the form of an explanation or excavation of information related to which aspects show the difference between users and non-users of Islamic fintech. This research was conducted because of the lack of research about the use of Islamic fintech in terms of various aspects above. This study contributes to the behavior of Indonesian people in utilizing Islamic fintech as a provider of Islamic financial services in the Industrial Revolution 4.0 era.Keywords: Islamic fintech, socioeconomic aspects, geographical aspects, social influence, religiosity